KAMPANYE MARI PEDULI TANPA ADANYA RASIS DI TENGAH PANDEMI - Andik Yulianto; Indra Saputra; Felix Fernando; Christian Christian; Eka Sucipto; Frenda Frenda; Hengki Hengki; Kelvin Oh; Jessica Angelyn; Olwin Olwin; Yanto Yanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
Indonesia is a multicultural country that is very vulnerable to discriminatory problems due to differences in race, ethnicity, culture, and religion. Self-awareness to stop racism is very important, especially in the middle of the COVID-19 pandemic. This paper presents the results of our activities to observe the opinions of the Batam community, especially about a sense of concern for others and about the issue of racism in the middle of a pandemic. Exploring opinions on the issue of racism is obtained by distributing questionnaires. A campaign of concern without being racist has been carried out with the aim of providing insight to the public on the importance of stopping racism.